INTEGRASI PASAR MODAL KAWASAN CINA - ASEAN - Santosa, Budi (Universitas Muhammdaiyah Surakarta, 2013)
This study aims to analyze the level of capital market integration ASEAN and China. Analysis tool used is Vector Error Correction Model (VECM). The results showed that capital markets of Malaysia, Philippines, Singapore, Thailand, and China have a positive effect on Indonesian capital markets, but the Indonesian capital market does not affect the capital markets of other countries. Singapore capital market has a positive effect on capital markets of Indonesia, Malaysia, Thailand, and China, except for the Philippines. Chinas capital market only affects the capital market in Singapore. Singapore capital market and China have complete integration because both affect each other. Philippine capital market only affects Indonesian capital market. Indonesian capital market is easily influenced by the fluctuation in capital markets in the ASEAN region and China. Singapore capital market is in a strong position. While the Philippine capital market are relatively more segmented.